Pengaruh Konsentrasi Biourine Untuk Meningkatkan Pertumbuhan Tanaman Kedelai (Glycine max (L.) Merill) - Sompotan, Saartje; Tulungen, Antje Grace; Tulung, Stella M. T.; Tumewu, Pemmy; Polii, Maria G.; Doodoh, Beatrix; Raintung, Jeane S. M.; Titah, Tilda; Porong, Jelie V.; Walingkas, Stanley A. F. (Sam Ratulangi University, 2024)
The purpose of the research was to study the effect of biourine on soybean plant growth, and to obtain the concentration of biourine that can increase soybean growth. To achieve the objectives, the research was designed using a completely randomized design. The treatments consisted of, A = No Biourine, B = 100 ml biourine/1 liter of water, C = 200 ml biourine/1 liter of water. Each treatment was repeated four times resulting in 12 experimental pots. The parameters observed were the number of leaves and the number of soybean branches. Data were analyzed using analysis of variance and 5% BNT test. The results showed that the application of biourine increased the growth of soybean plants as indicated by plant height and the number of leaves with three branches. The concentration of 100 ml biourine/1 liter of water increased the growth of soybean plants.